Listening Comprehension Problems: The Pre-Diploma Students’ Insights and Experiences - Abu Bakar, Azrina binti (Journal of ELT Research, 2019)
Despite the fact that listening is one of the fundamental skills to develop in English language learning, most of the pre-diploma students at Universiti Teknologi Mara (UiTM) Cawangan Melaka often regard listening as a difficult skill to learn. However, little research has been conducted regarding the listening comprehension problems that they experienced in English class. This paper, thus investigates the pre-diploma students’ insights into English listening difficulties that they encountered in listening comprehension and explored numerous effective listening strategies to improve their English listening abilities. 80 pre-diploma students who took the Pre-Diploma English Language course were selected randomnly for the study. Data collections included 5-point Likert type questionnaire and semi-structured interviews. Results suggest that the main problems highlighted by most students are linked to the speed of speech, text length, vocabulary knowledge, and unfamiliar accents.